1998
DOI: 10.1086/517405
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination ofMycobacterium tuberculosisacross the San Francisco Bay Area

Abstract: The propensity of Mycobacterium tuberculosis genotypes to spread across geographic boundaries was investigated by comparing the IS6110 and polymorphic GC-rich sequence patterns of M. The modern age of transportation has brought unprecedented rated countries and spread of multidrug-resistant organisms between distant domestic sites have been demonstrated, spread movement of large numbers of people across geographic boundaries, heightening concerns about the global disseminaof M. tuberculosis between geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…Multivariate analyses indicated that alcohol abuse was the strongest risk factor associated with recent transmission in Hamburg. This is somewhat surprising, since in several international reports published so far (1,4,10), alcohol abuse has not been identified as an independent predictor for recent transmission. Further independent risk factors for being in an IS6110 cluster are a history of contact tracing and unemployment, whereas being male, being homeless, testing positive for sputum smear, living as a drug addict, or suffering from AIDS was not significantly associated with clustering in multivariate analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Multivariate analyses indicated that alcohol abuse was the strongest risk factor associated with recent transmission in Hamburg. This is somewhat surprising, since in several international reports published so far (1,4,10), alcohol abuse has not been identified as an independent predictor for recent transmission. Further independent risk factors for being in an IS6110 cluster are a history of contact tracing and unemployment, whereas being male, being homeless, testing positive for sputum smear, living as a drug addict, or suffering from AIDS was not significantly associated with clustering in multivariate analysis.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, other important key components of TB control are the improvement of case finding among persons presenting with symptoms of TB, especially in HIV-infected individuals, by providing better access to quality-assured TB sputum microscopy as well as the Directly Observed Therapy Short-Course strategy in TB treatment. The latter achieves higher cure rates by an uninterrupted supply of antituberculotic drugs in a standardised short-course chemotherapy under direct observation [2].By applying classical epidemiological and molecular strain-typing techniques, population-based studies have recently revealed a high frequency of transmission of MTB, even in countries with a low TB incidence [3][4][5][6][7]. The tuberculin skin test (TST) introduced by Mantoux has been widely used as a screening test to identify individuals with LTBI.…”
mentioning
confidence: 99%
“…By applying classical epidemiological and molecular strain-typing techniques, population-based studies have recently revealed a high frequency of transmission of MTB, even in countries with a low TB incidence [3][4][5][6][7]. The tuberculin skin test (TST) introduced by Mantoux has been widely used as a screening test to identify individuals with LTBI.…”
mentioning
confidence: 99%
“…Of the 24 genes, 19 were monomorphic and the last five appeared slightly polymorphic (only six polymorphic nucleotide sites on all five genes). On the contrary, the transposable elements show high levels of genetic polymorphism, and they are widely used for studying the genetic variability in the MTB species [17,95,173] (see below for more details). Nevertheless, the only way to detect the real genetic diversity of an organism is the whole sequencing of several genomes from different clinical isolates.…”
Section: Genome and Genetic Diversity Of Mtbmentioning
confidence: 99%